HEAVEN versus LEMON Score in Predicting Emergency Intubation Success in Critically Ill Patients - Johan, T. Abdurrahman; Lubis, Andriamuri Primaputra; Ihsan, Muhammad (JAI (Jurnal Anestesiologi Indonesia), 2026)
Background: The LEMON and HEAVEN scores are currently used only to assess airway difficulties in emergency patients. This research was conducted to evaluate the success of emergency intubation using the LEMON and HEAVEN scores in critically ill patients who require mechanical ventilation.Objective: The objective of this study is to compare the success of emergency intubation with the HEAVEN score with the LEMON score in critically ill patients requiring mechanical ventilation.Methods: This research employed a cross-sectional observational analytical design and took place at Adam Malik General Hospital, Medan, Dr. Pirngadi Medan, and RSU Haji Medan from January to March 2024. All critically ill patients aged 18-64 years requiring emergency intubation were included, excluding those with prior tracheotomy or intubation experience who refused to participate. A minimum sample size of 70 participants was obtained, with statistical analysis planned using SPSS version 26 software.Results: A total of 76 patients were included in this study. According to the LEMON score, 5 patients (6.6%) were identified as having difficult intubation, whereas the HEAVEN score categorized 30 patients (39.5%) as difficult cases. Following emergency intubation, only 3 patients (3.9%) experienced initial intubation failure. The LEMON score demonstrated an area under the curve (AUC) of 0.984, indicating excellent accuracy, while the HEAVEN score had an AUC of 0.911, also demonstrating excellent accuracy. Both scores proved equally effective in assessing intubation success, with statistical analysis favoring the superiority of the LEMON score. However, the HEAVEN score can serve as a viable alternative in critically ill patients.Conclusion: The LEMON score and HEAVEN score can be used to evaluate the success of emergency department intubation in critically ill patients who require mechanical ventilation.